Plasmonic Nanostructures Basic Concepts, Optimization and Applications - Steglich, Patrick (IntechOpen, 2023)
Plasmonics includes the fundamentals of surface plasmon polaritons in metals, and its rapidly increasing applications in biochemistry, nanotechnology, optical communication, sensing, and medicine. Surface plasmon polaritons have become popular because of their ultrasensitive optical measurement capabilities, and in recent years they have also been employed for ultra-high-speed data transfer. This book presents recent advances in the broad field of plasmonics, covering not only current progress and the latest breakthroughs in emergent applications but also geometry optimizations and the fundamentals of physical interactions.